BUDGET IMPACT ANALYSIS OF PERAMPANEL FOR ADJUNCTIVE TREATMENT IN EPILEPSY PATIENTS 12 YEARS OF AGE AND OLDER FOR PARTIAL ONSET SEIZURES WITH OR WITHOUT SECONDARY GENERALIZATION AND PRIMARY GENERALIZED TONIC-CLONIC SEIZURES IN THE RUSSIAN FEDERATION - V. R. Mkrtchyan; A. M. Sergeev; K. I. Pochigaeva; I. A. Shpak (IRBIS LLC, 2016)
Objectives. To assess the incremental budget impact (BI) of using of utilizing perampanel to treat partial-onset seizures (POS) and primary generalized tonic-clonic seizures (PGTCS) in patients who are 12 years of age and older in Russia.Methods. The budget impact was estimated by comparing two different scenarios: Cost of POS & PGTCS without Perampanel and Cost of POS & PGTCS with Perampanel (Perampanel Adoption). In the latter scenario, market share of perampanel was assumed to increase every year for up to five years. The model was developed from a payer perspective with a time horizon of five years. Direct costs included drugs and medical resources (hospitalization, emergency care costs, visits to physician). BI was calculated as the difference in costs between Perampanel Adoption scenario and the cost without Perampanel.Results. In Russia, approximately 125,499 patients who are at least 12 years old are treated for refractory POS & PGTCS each year. The market share of perampanel in the perampanel adoption scenario from year 1 to year 5 was 0.1%, 0.5%, 1.0%, 2.0% and 3.0%, respectively. During the same period, the adoption of perampanel is projected to increase drug costs (in millions) by RUB15.2 (1.2%), RUB76.1 (6.2%), RUB152.4 (12.3%), RUB305.4 (24.7%), and RUB459.0 (37.0%), respectively. A significant portion of the 5-year cumulative increase in drug costs (RUB 1,008 million) will be offset by a decrease in non-drug medical resources (-RUB152.7 million). The cumulative budget impact from perampanel adoption for the first five years is projected to be RUB855 million (0.7%), with an additional 231 patients gaining seizure freedom over a period of 5 years from the adoption of perampanel.Conclusion. Perampanel should be considered as an alternative alongside current antiepileptic drugs in patients with symptoms refractory to prior antiepileptic treatments.